2020
DOI: 10.3390/ijerph17176129
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Findings of Alcohol Misuse and Dependence Symptoms among Adolescent Girls and Young Women Involved in High-Risk Sexual Behavior in Kampala, Uganda

Abstract: Alcohol-related harms may be increased among adolescent girls and young women (AGYW) involved in sex work, yet data on alcohol misuse among AGYW in sub-Saharan Africa are still scarce. We conducted a cross-sectional study among 15–24-year-old AGYW from January 2013 to December 2018 in Kampala, Uganda and used the Alcohol Use Disorder Identification Test (AUDIT) to study alcohol use patterns and dependence symptoms (dependence score ≥4). Of 1440 participants (median age 21 years), 83.1% had less than secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
7
15
0
Order By: Relevance
“…Alcohol dependent individuals tended to spend a long time away from their homes, which exposes them to meeting new people who may become sexual partners [ 50 ]. This is consistent with results reported by several studies that have indicated a correlation between alcohol dependency and high-risk sexual behavior among young people [ 51 , 52 ] and older populations at risk [ 53 , 54 ]. If aware of such risk, persons dependent upon alcohol may be more aware of the available methods that may protect them from contracting HIV.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Alcohol dependent individuals tended to spend a long time away from their homes, which exposes them to meeting new people who may become sexual partners [ 50 ]. This is consistent with results reported by several studies that have indicated a correlation between alcohol dependency and high-risk sexual behavior among young people [ 51 , 52 ] and older populations at risk [ 53 , 54 ]. If aware of such risk, persons dependent upon alcohol may be more aware of the available methods that may protect them from contracting HIV.…”
Section: Discussionsupporting
confidence: 93%
“…We screened 532 AGYW for both study participation and PrEP eligibility, 94 were not eligible for PrEP due to: HIV sero-positivity [ 29 ], not sexually active in the past 3 months [ 51 ], hepatitis B infection [ 10 ] and abnormal kidney function tests [ 4 ]. Of the rest, 153 were not eligible for the study due to: study sample size being achieved (93) and unwillingness to return for follow up procedures and other reasons (60).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol dependent individuals tended to spend a long time away from their homes, which exposes them to meeting new people who may become sexual partners (44). This is consistent with results reported by several studies that have indicated a correlation between alcohol dependency and high-risk sexual behavior among young people (45,46) and older populations at risk (47,48). If aware of such risk, persons dependent upon alcohol may be more aware of the available methods that may protect them from contracting HIV.…”
Section: Discussionsupporting
confidence: 86%
“…Both studies showed alcohol use as a significant correlate of reporting multiple forms of violence. We have also previously shown in a study that recruited young women, that excessive alcohol consumption was associated with IPV victimization (Mayanja et al, 2020). The association between excessive alcohol use and IPV victimization is bi-directional.…”
Section: Discussionsupporting
confidence: 61%